1988
DOI: 10.1002/1098-108x(198803)7:2<177::aid-eat2260070204>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology associated with bulimia, binge eating, and obesity

Abstract: Bulimic binge‐purgers, bulimic binge‐eaters, nonbulimic obese presenting for treatment for obesity, obese not in treatment, and normal control subjects were compared using the Minnesota Multiphasic Personality Inventory (MMPI), Symptom Checklist‐90‐Revised (SCL‐90‐R), and Beck Depression Inventory (BDI). Results suggested a continuum of severity, with the binge‐purger group showing the highest levels of psychopathology, and the binge‐eaters and clinical obese showing significantly more distress than the two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
3

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 20 publications
6
46
0
3
Order By: Relevance
“…Parallel findings were reported from controlled studies with obese control subjects (8,45) or with non-obese patients presenting for general medical treatment (46). Again, in contrast to these findings, most population-based studies found only weak or inconsistent associations between general psychopathology and categorical or continuous (e.g., BMI) measures of obesity (47).…”
Section: Associations Between Obesity and General Psychopathologysupporting
confidence: 53%
See 1 more Smart Citation
“…Parallel findings were reported from controlled studies with obese control subjects (8,45) or with non-obese patients presenting for general medical treatment (46). Again, in contrast to these findings, most population-based studies found only weak or inconsistent associations between general psychopathology and categorical or continuous (e.g., BMI) measures of obesity (47).…”
Section: Associations Between Obesity and General Psychopathologysupporting
confidence: 53%
“…Depending on differences in sampling, diagnostic criteria, diagnostic coverage, age composition, and culture, numerous clinical studies demonstrate almost consistently up to 4.8 times higher prevalence rates of mental disorders (5,6) as well as an elevated general psychopathology (7,8) in obese patients compared with non-obese nonpatients. A major problem of studies with obese patients is the uncertainty of whether obesity or other factors contribute to a higher degree to the increased psychopathology (9).…”
Section: Introductionmentioning
confidence: 99%
“…Dykens and Gerrard's (1986) study of 424 undergraduate women, bulimics, repeat dieters, and controls differed on body esteem, supporting the continuity perspective. In contrast, Prather and Williamson (1988) found that depression levels did not differentiate 16 bulimic binge-purgers, 16 bulimic binge-eaters, 16 nonbulimic obese presenting for obesity treatment, 16 obese not in treatment, and 16 female undergraduate controls. Most work in this area has been conducted with female student populations (Dykens & Gerrard, 1986;Ruderman & Besbeas, 1992;Stice et al, 1998) and has focused predominantly on bulimia and various comparison groups, including (1) dieters and nonsymptomatic individuals (Ruderman & Besbeas, 1992); (2) current dieters, restrained dieters, and unrestrained nondieters (Lowe et al, 1996); (3) severe binge eaters, moderate binge eaters, mild binge eaters, and nonbinge eaters (Vanderheyden & Boland, 1987); and (4) binge/purgers, binge eaters, and controls (Prather & Williamson, 1988).…”
Section: Introductionmentioning
confidence: 75%
“…Stice and colleagues (1998) suggested that future research should attempt to include larger samples of bulimic women to have increased statistical power and reliability of effects. In addition, in contrast to most research in this area that has included primarily high school and college age women (Dykens & Gerrard, 1986;Prather & Williamson, 1988), this study included women ranging from 27-41 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation